1993
DOI: 10.1002/lsm.1900130309
|View full text |Cite
|
Sign up to set email alerts
|

Fluorospectral study of the rat brain and glioma in vivo

Abstract: An animal model of cerebral glioma was utilized by implanting C6 glioma cells into the brains of adult Wistar rats. Once tumors developed to 7-12 mm in diameter, we conducted continuous fluorimetry monitoring of glioma up to 24 hours using a fibre-optic system connected to an intensified multichannel photodetector after an intravenous injection of hematoporphyrin derivative (HPD) into the rats. The intensity of the fluorescence in normal brain reached a plateau 6 hours after intravenous injection of HPD while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Consequently, the current strategies are to resect the tumor as much as possible without inducing fur-ther neurological deficit of the patient, and then follow with adjuvant therapies such as radiation therapy, interstitial brachytherapy, and chemotherapy. In our previous study, we demonstrated that the ratio of the amount of HPD between glioma and brain was 6.1, whereas the ratio between brain adjacent to tumor and brain was 3.9 [13]. In this study, we showed that ALA-PDT could effectively kill glioma cells in vitro.…”
Section: Ala-mediated Pdt Is Effective For U-105mg Glioma Cellsmentioning
confidence: 53%
“…Consequently, the current strategies are to resect the tumor as much as possible without inducing fur-ther neurological deficit of the patient, and then follow with adjuvant therapies such as radiation therapy, interstitial brachytherapy, and chemotherapy. In our previous study, we demonstrated that the ratio of the amount of HPD between glioma and brain was 6.1, whereas the ratio between brain adjacent to tumor and brain was 3.9 [13]. In this study, we showed that ALA-PDT could effectively kill glioma cells in vitro.…”
Section: Ala-mediated Pdt Is Effective For U-105mg Glioma Cellsmentioning
confidence: 53%
“…Exogenous fluorophores including 1) fluorescent photosensitizers, 59–67 2) fluorescent dyes, 69,70 3) fluorophortagged cancer‐specific antibodies 71 and 4) macromolecular carriers 65 are being investigated as agents to enhance fluorescence contrast of superficial and deeply seated cancers. Relative cancer selection for diagnosis and treatment is based on accumulation peaks appearing in the tumor at a different time than in the surrounding tissues.…”
Section: Use Of Exogenous Fluorophores For Optical Diagnosis Of Cancersmentioning
confidence: 99%
“…Fluorescence spectroscopy has already been proposed as a diagnostic technique for the intraoperative delineation of tumor resection margins based on the emission properties of both exogenous (15–18) and endogenous (19–22) fluorophores.…”
Section: Introductionmentioning
confidence: 99%